David Friedrich Strauss: reputation and reality. (2nd January 2020) - Beiser, Frederick
ABSTRACT: Because of his radical critique of Christianity, David Friedrich Strauss has often been portrayed as a political radical, as a revolutionary on the far left of the Hegelian school. A closer look at his actual historical views shows that his political and religious views were much more moderate. Rather than wanting to destroy Christianity, he wanted to preserve it; and instead of standing on the far left of the political spectrum, Strauss stood in its centre.